2019
DOI: 10.17645/mac.v7i3.1911
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Emotions and Affective Investments in War: RT and the Syrian Conflict on YouTube

Abstract: Within the context of an ‘affective turn’ in media studies and the social sciences, this article explores the methodological challenges of researching emotions when studying online videos of conflict. Our study focuses on videos of the Syrian conflict shared on YouTube by the Russian state funded international broadcaster, RT. We propose that the concept of affective investment is a useful pivot between online videos of conflict and audience responses to them. Our study interrogates the role that affective inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…Unsurprisingly, its viewers, like for most international news channels, tend to skew toward highly educated males” (Orrtung and Nelson 2019: 14). A study of YouTube comments made in response to RT videos about the Syrian conflict found that the sample of audiences analyzed tended to support the broadcaster’s characterization of the conflict and expressed support for Russia alongside anger and mistrust of the “West” (Chatterje-Doody and Crilley 2019a: 174). Richter (2017: 13) characterizes RT’s audience as comprised of people who support conspiracy theories because they are “distrustful” of “mainstream media.” Similarly, Birrell (2018) suggests that RT’s online audiences are vulnerable to the “malign force” of its media content, and are situated on the fringes of mainstream politics, attracted to niche interests and incendiary ideas, as well as anti-American and anti-“Western” discourse.…”
Section: Rt’s Operational Paradigms: Reviewing the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, its viewers, like for most international news channels, tend to skew toward highly educated males” (Orrtung and Nelson 2019: 14). A study of YouTube comments made in response to RT videos about the Syrian conflict found that the sample of audiences analyzed tended to support the broadcaster’s characterization of the conflict and expressed support for Russia alongside anger and mistrust of the “West” (Chatterje-Doody and Crilley 2019a: 174). Richter (2017: 13) characterizes RT’s audience as comprised of people who support conspiracy theories because they are “distrustful” of “mainstream media.” Similarly, Birrell (2018) suggests that RT’s online audiences are vulnerable to the “malign force” of its media content, and are situated on the fringes of mainstream politics, attracted to niche interests and incendiary ideas, as well as anti-American and anti-“Western” discourse.…”
Section: Rt’s Operational Paradigms: Reviewing the Literaturementioning
confidence: 99%
“…It can also be done without reciprocation, which means that it is not dependent upon anyone else (as with two-way ties on platforms such as Facebook). Twitter followers are not equivalent to a traditional broadcast audience, nor even to the engaged “active” audiences who comment on YouTube videos (Chatterje-Doody and Crilley 2019a; Crilley and Chatterje-Doody 2020a, 2020b). Indeed, a user might follow an account but never engage with it—and simply forget to unfollow it.…”
Section: Rt’s Operational Paradigms: Reviewing the Literaturementioning
confidence: 99%
“…Finally, the tendency to focus on viral, humorous, potentially controversial content, such as Pogba’s trolling of English fans and Maradona’s eccentric behaviour as well as Internet responses to it, extends RT’s usual practice of attempting to provoke an emotional reaction from audiences, thus boosting online discussion and viewership (Chatterje-Doody and Crilley, 2019; Miazhevich, 2018). RT journalists confirmed that the sports desk, both during the World Cup and beyond it, would aim not only to break the news to their audiences as quickly as possible, but also to ‘write our [stories] in a way that would get our audience to interact’ (Armstrong, 2020, Interview).…”
Section: Interpreting Rt’s Representation Of Russiamentioning
confidence: 99%
“…Based on a contrast study of letters to tabloid and mainstream newspapers, Smith and Adendorff (2014) reveal readers’ affiliation around a bond with valuation concerning the topic of education. Chatterje-Doody and Crilley (2019), adopting the concept of “affective investments”, explore online audiences’ emotional reactions to media images of war. These studies provide a general picture of textual patterns or emotional tracks in relation to readers’ response to news.…”
Section: Appraisalmentioning
confidence: 99%